Embedding Character Education through School Culture in Islamic Junior High Schools: A Qualitative Study of Religiosity, Honesty, Tolerance, and Discipline - Chadija Chadija; Kasim, Amrah; Achruh, Andi; Syamsuddin Syamsuddin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study investigates how character education is embedded into the school culture of an Indonesian Islamic junior high school (madrasah), focusing on four core values: religiosity, honesty, tolerance, and discipline. Using a qualitative naturalistic approach, the research was conducted at MTsN 3 Halmahera Utara through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, and students. The findings reveal that character education at the madrasah is not a standalone program but is institutionalized through consistent routines, religious practices, and role modeling. Religiosity is fostered through structured worship, integration of Islamic values into lessons, and spiritual habits. Honesty is promoted via trust-based learning environments, teacher exemplarity, and reinforcement of moral norms. Tolerance is cultivated through inclusive social interactions and respect for religious and cultural differences, while discipline is internalized through habitual rule-following, punctuality, and self-regulation. These findings align with existing theories and regional character education frameworks, confirming that character is best formed through embedded cultural processes and consistent adult exemplarity. The study contributes to the understanding of how Islamic schools can function as moral communities and highlights the importance of alignment between school culture, family support, and wider social contexts in achieving sustainable moral development.